Evaluation of reverse logistics contributions and impacts on sustainable development - Oliveira, Maquele Antunes de (2023)
Global concern around sustainable development has increased and production practices that can contribute to this have gained prominence – with reverse logistics (RL) being one of these. However, the topic is still emerging and requires new efforts. The definition of which contributions reverse logistics can bring to sustainability is still inexact. The research aim is to extend the understanding of the sustainable impacts that RL can generate economically, environmentally and socially and to define which SDGs (Sustainable Development Goals) are the most impacted by RL adoption. In addition, it is intended to contribute to the production of knowledge related to RL and sustainability in its three dimensions – where there is a lack of studies –; demonstrate to companies interested in increasing their adherence to the global SDG pact how the adoption of RL can benefit them; identify the main impacts of RL for sustainable development and elucidate how RL adoption can help the achievement of the SDGs. For these purposes, the research will make use of: (i) a systematic literature review in order to gather the empirical evidence of RL impacts on sustainability, (ii) expert elicitation through the IDEA protocol to evaluate the relation between RL and the SDGs and (iii) VIKOR to the analysis and to define which SDGs are the most impacted by the adoption of RL practices. It was found in literature that: the environmental pillar of sustainability is the one with more impacts reported; the social pillar still has minimum impacts reported – even with the great social contributions pointed for human welfare – and the RL impact most cited in literature was “improve profit and cost savings”. After the analysis in the second article presented in this dissertation, it was found that SDG 12 has the greatest contribution from RL adoption and SDG 1 is the one which has its accomplishment least driven by RL. At the end, instructions for further research are given.